2016
DOI: 10.1248/cpb.c16-00501
|View full text |Cite
|
Sign up to set email alerts
|

Dichloromaleimide (diCMI): A Small and Fluorogenic Reactive Group for Use in Affinity Labeling

Abstract: Chemical probes comprising a ligand moiety, a reactive group (e.g. epoxide, haloacetyl or photoreactive group) and a tag unit (e.g. fluorophore or radioisotope) are widely used in affinity labeling to identify the target proteins of bioactive molecules. However, design and synthesis of highly functionalized chemical probes are often time-consuming. In this paper, we propose a simple design strategy for chemical probes bearing a small 2,3-dichloromaleimide (diCMI) unit, which serves as a combined reactive group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…These results demonstrated that the N -glycan of PYP-GLUT4 is involved in quality control of PYP-GLUT4 and dictates the pathway PYP-GLUT4 takes within the cell. While these observations are in agreement with previous reports that indicated that the N -glycan plays an important role in quality control of PYP-GLUT4 WT , 34 this is the first report that actually visualized the distribution of different types of PYP-GLUT4 molecules within a live cell using fluorescent probes of different wavelengths.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results demonstrated that the N -glycan of PYP-GLUT4 is involved in quality control of PYP-GLUT4 and dictates the pathway PYP-GLUT4 takes within the cell. While these observations are in agreement with previous reports that indicated that the N -glycan plays an important role in quality control of PYP-GLUT4 WT , 34 this is the first report that actually visualized the distribution of different types of PYP-GLUT4 molecules within a live cell using fluorescent probes of different wavelengths.…”
Section: Resultssupporting
confidence: 93%
“…Based on these results, we concluded that the most suitable ligand structure for the new probe would be 5, which employed a chloroacetyl group at the reactive site and a trifluoromethyl group within the ligand portion. The reason 5 exhibited high reactivity against PYP-tag was thought to be due to the electron-withdrawing trifluoromethyl functionality elevating the reactivity of the chloroacetyl group 34 and noncovalent interaction between PYP-tag and 5 that is absent in glutathione. Thus, incorporation of those structural features into the novel probe design was expected to accelerate the labeling reaction rate of the probe.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, design and synthesis of highly functionalized chemical probes are often time-consuming. [9][10][11] To address this issue, we recently presented a simple design strategy for chemical probes bearing only a small alkoxy nitrobenzoxadiazole (O-NBD, 180 Da), 12) 2,3-dichloromaleimide (diCMI, 164 Da) 13) or 4-azidophthalimide (AzPI, 189 Da) 14) tag, each of which can serve as a combined reactive group and tracer unit. The AzPI tag is particularly useful for identifying target proteins of bioactive small molecules because it generates highly reactive nitrene species under photo-irradiation conditions and is capable of forming a covalent bond with various amino acids.…”
mentioning
confidence: 99%